Unlocking the universe - Hawking, Stephen (Puffin, 2021)
Have you ever wondered how the universe began? Or what it takes to put humans on the moon - or even on Mars? What would you do if you could travel through space and time? Embark on the adventure of a lifetime in this beautiful collection of up-to-the-minute essays mind-blowing facts and out-of-this-world colour photographs, by the world's leading scientists including Professor Stephen Hawking himself, curated by the brilliant Lucy Hawking.